Penerapan Inovasi Produksi pada Sulaman Kapalo Samek Hasanah di Kota Bukittinggi - Ma'ruf Ma'ruf; Ratni Prima Lita; Verinita Verinita; Sari Surya; Budi Rahmadya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Embroidery is one of the superior products of the tourist city of Bukittinggi, West Sumatra. The classic industrial problems of artisans are low production capabilities and lack of innovation. This is exacerbated by the decreasing number of artisans and production systems that is still carried out traditionally. The application of product innovation in the Kapalo Samek Embroidery Group is carried out by a combination of recruitment programs for new craftsmen through training and training in motif design, both manual and digital, as well as registration of motif designs as Intellectual Property Rights (IPR). This activity has succeeded in recruiting 60 new craftsmen, and 25% of them have been able to produce standard embroidery within two months. Furthermore, craftsmen also have knowledge and skills in improving the quality of motif designs and being able to use Adobe Photoshop software to produce new designs. As a work of art, the design of the motif created has been registered by the craftsmen to obtain IPR. The results of this activity were believed to have strengthened the capacity of the artisan groups to increase production and impact their economic conditions.